PENGARUH LITERASI KEUANGAN DAN LITERASI DIGITAL TERHADAP KINERJA KEUANGAN UMKM DIKECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - Nasriani, Nasriani; Salida, Amrizal; Rahman, Usman (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
The purpose of this study is to determine the influence of financial literacy and digital literacy on the financial performance of MSMEs. The analytical method used in this study is path analysis. The research sample uses a nonprobability sampling approach with the Accidental Sampling technique, while the sampling formula used is the Lemshow method with a sample size of 96 respondents. Based on the coefficient of determination (R Square) of 0.428 (42.8%). The first hypothesis is that financial literacy has a positive and significant effect on financial performance partially with a calculated T value of 4.580> 1.661 T table. And digital literacy has a positive and significant effect on financial performance partially with a calculated T value of 5.209> 1.661 T table. Finally, with a calculated F value of 34.792> 3.090 F table, financial literacy and digital literacy significantly and positively influence financial performance simultaneously.